The vocabulary mastery for early childhood through songs - Djoko Sri Bimo; Maria Yustina Rensi Dartani (Universitas PGRI Semarang, 2021)
The study was an experimental study that aims to improve early childhood’s education students in English vocabulary skills through interactive songs learning method for early childhood at PAUD Tarbiyatul Athfal 49, that was located in Kuripan, Ngadirgo village, Mijen district, Semarang. The study involved two groups of students, those were the control group (25 students) who were taught by using pictures, and the experimental group (25 students) who were taught by using songs. The pre-test was given before the treatment began and the post-test was carried out after the experiment was finished. The null hypothesis was then drawn, and T-test was also conducted to compare the mean score of the two groups. The mean score of the control group was 13.3, while the mean score of the experimental group was 16.4. The results showed that the mean score of the experimental group was higher than the control groups The t-test that had been carried out also showed that there were significant difference between the two groups was 0,23 (the figure was above 0,5). Based on the above results, it proved that Tarbiyatul Athfal early childhood education students understood in English by using songs was better than other learning method, since songs can motivate them to know more about English vocabulary